Node localization algorithm for detecting malicious nodes to prevent connection failures and improve end-to-end delay - Kumar, G. Hemanth; G.P., Ramesh (Computer communications, 2022)
In sensor network applications, the measured data makes sense only if the location is known. The location of the node is known, and the wireless communication line and transmission method between the two nodes can be an unknown collaboration process where a sensor with a known location is used to locate the node in an unknown location. Various localization algorithms are available that use linear and nonlinear methods to find nodes. Security is a major issue in localization. After the data is sent from the beacon node to the binding node, an error occurs because the virus-safe or unsafe mobile beacon acts like the original mobile beacon, sending the wrong message. One of the basic problems of wireless sensor networks is the localization and security of nodes. This article analyses the performance of optimization algorithms like Ant Colony Optimization algorithms, opportunity routing algorithms, and the proposed Buffalo optimization algorithm. The performance of the buffalo algorithm is compared with these optimization algorithms. Performance metrics such as throughput, residual energy, packet forwarding rate, packet loss rate, delay, and cost were measured. Then the algorithm is implemented as a hardware system for measuring system performance in real-time. Based on a detailed analysis of the performance of optimization algorithms in wireless sensor networks, the buffalo algorithm provides higher efficiency and performance in wireless sensor network applications.